The 2nd International Electronic Conference on Water Sciences 2017
DOI: 10.3390/ecws-2-04957
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical Formation of Hydrogen Peroxide

Abstract: Abstract:The work detailed in this study utilized 20 kHz ultrasonic irradiation as a mechanism of hydrogen peroxide production. The effects of various operating parameters were investigated, including ultrasonic intensity; solution pH; source of water; initial dibutyl phthalate concentration and the presence of hydrogen peroxide. During the irradiation, the H2O2 concentration was monitored. The results indicate that H2O2 is produced by cavitation during ultrasonic irradiation. An increase in ultrasonic intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
(55 reference statements)
2
16
0
Order By: Relevance
“…Although studies have shown that US supports creation of H 2 O 2 especially in presence of O 2 and that O 2 can conserve • OH radicals to generate other oxidizing species like • O and OH2 [35,36], the results under the conditions tested here are in an agreement with other studies showing negative effect on H 2 O 2 formation. For example, Ziembowicz et al found that initial H 2 O 2 plays a crucial role in the effectiveness of the combined process (similar to the combined process used here) [52]. It was found that when initial concentration of H 2 O 2 increases above 0.1 mM (compared to 0.3 mM formed under tested conditions here), the amount of H 2 O 2 formed under US decreases significantly.…”
Section: Resultssupporting
confidence: 52%
“…Although studies have shown that US supports creation of H 2 O 2 especially in presence of O 2 and that O 2 can conserve • OH radicals to generate other oxidizing species like • O and OH2 [35,36], the results under the conditions tested here are in an agreement with other studies showing negative effect on H 2 O 2 formation. For example, Ziembowicz et al found that initial H 2 O 2 plays a crucial role in the effectiveness of the combined process (similar to the combined process used here) [52]. It was found that when initial concentration of H 2 O 2 increases above 0.1 mM (compared to 0.3 mM formed under tested conditions here), the amount of H 2 O 2 formed under US decreases significantly.…”
Section: Resultssupporting
confidence: 52%
“…Analysis of the S 2-/Mo 4+ ratios from high resolution XPS data (Table 1) demonstrates that there are no significant changes in the ratio from the bulk 2H phase to the various samples with higher films. 27,32,33 The temperature dependence and magnitude of this effect under our conditions therefore needs to be established.…”
Section: Origins Of the Conductivitymentioning
confidence: 99%
“…The results are presented in Figure 3a. The use of hydrogen peroxide was omitted in order to minimize the risk of oxidation process inhibition by an excessive quantity of H2O2, which may result in • OH radical recombination and the auto-decomposition of H2O2 into H2O and O2, as evidenced [42][43][44]. Based on the obtained results, it was concluded that the decolorization degree depends on the initial dye concentration.…”
Section: Combined Pds/o3/uvmentioning
confidence: 99%